Compressive stress and its impact on the gas diffusion layer: A review. (19th January 2022) - Shi, Qitong; Feng, Cong; Ming, Pingwen; Tang, Fumin; Zhang, Cunman
Abstract: The gas diffusion layer is subjected to several mechanical stresses during the manufacturing and application processes of fuel cell. The deformation of gas diffusion layer under compression affects the mass transfer and electron migration between the flow channel and reaction area. This paper mainly reviews the published research on stress distribution of the gas diffusion layer, the effects of compressive stress on the bulk and pore characteristics of the gas diffusion layer, and the performance of fuel cell. Furthermore, the relationship between stress and strain of the gas diffusion layer is summarized. The impacts of compression on the gas diffusion layer present the characteristics of multi-parameters, non-linearly, small variation and strong coupling. This review suggests that the compression affects the pore and bulk characteristics of gas diffusion layer should be comprehensively investigated. Highlights: The stress distribution of GDL is non-uniform and cannot be ignored. The stress-strain relationship of gas diffusion layer is summarized. The impacts of compression on the GDL should be comprehensively investigated.